Third Five Year Plan Fourth Year’s (1964-65) Progress Report - Planning Commission (Planning Commission, 1966)
This publication is intended to review the progress of the third five year plan during the fourth year of its implementation (1964-65). the total budget provision under the State Plan for the year was Rs. 4436.62 lakhs. This provision was later restricted to Rs. 3998.67 lakhs. Against this restricted outlay an amount of Rs. 4007.72 lakhs was spent during the year. In this volume an attempt has been made to give the physical achievements under various schemes as on 31-3-1965. The over-all achievement at the end of the year 1964-65 under each head of development has been furnished in separate column at the beginning of the write-up relating to each development head.
Progress Report